2021
DOI: 10.56499/jppres20.928_9.1.78
|View full text |Cite
|
Sign up to set email alerts
|

The component analysis of liquid smoke from rice hulls and its toxicity test on baby hamster kidney cells

Abstract: Context: The pyrolysis product of rice hulls (Oryza sativa) has been used for the natural preservation of food and shows the potential to act as an antioxidant and anti-inflammatory product. However, the safety of this treatment has still not been studied. Aims: To analyse liquid smoke derived from rice hulls (Oryza sativa) components, its physical characteristics including acidity, density, and its toxicity on baby hamster kidney (BHK) cells. Methods: The physical characteristics of acidity and density were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Liquid smoke has been confirmed as a safe material. It was confirmed that a 10% concentration of liquid smoke derived from rice hull showed the highest living cells in vitro (Arundina et al, 2021c). In vivo, it was also confirmed that liquid smoke from rice hull had a lethal dose value >15,000 mg/kg body weight, categorizing it as a relatively harmless substance (Arundina et al, 2020b).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Liquid smoke has been confirmed as a safe material. It was confirmed that a 10% concentration of liquid smoke derived from rice hull showed the highest living cells in vitro (Arundina et al, 2021c). In vivo, it was also confirmed that liquid smoke from rice hull had a lethal dose value >15,000 mg/kg body weight, categorizing it as a relatively harmless substance (Arundina et al, 2020b).…”
Section: Discussionmentioning
confidence: 86%
“…Both CS-LS and liquid smoke from rice hulls are rich in phenolic components. The physical characteristics are similar: CS-LS has an acidity of 2.39 (Surboyo et al, 2019b), and liquid smoke from rice hull has an acidity of 2.296 (Arundina et al, 2021c). Liquid smoke has a pH range between 2.5 and 3.1 and is presumed to have carcinogenic properties; however, it has been shown to have non-toxic and therapeutic effects (Maryam, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Liquid smoke is a product of the process of breaking wood structures with high temperature. 4 Several ingredients in Indonesia that can be used to produce liquid smoke include rice husks, 5 coconut shells, 6,7 durian, 8 lamtoro, corn comb, 9 bamboo, 10 and cocoa bean skin. 11 Of these various types of materials, rice husks have been shown to have the potential to treat various diseases, including periodontitis, 12 oral ulcer, [13][14][15][16] diabetes, 17,18 and burn.…”
Section: Introductionmentioning
confidence: 99%
“…11 Of these various types of materials, rice husks have been shown to have the potential to treat various diseases, including periodontitis, 12 oral ulcer, 13 14 15 16 diabetes, 17 18 and burn. 19 The liquid smoke rice hull contains phenol, 2-methoxy-phenol, mequinol, 6-octadecenoic acid, oleic acid, and 9-octadecenoic acid 5 that possess the analgesic, 20 anti-inflammation, 14 antibacterial, 12 21 and lower toxicity. 5 22 The liquid smoked rice husk is widely used by Indonesian as natural preservative for fish 23 24 and meat.…”
Section: Introductionmentioning
confidence: 99%